Intervensi Kesehatan dengan Media Video Tutorial terhadap Pengetahuan Ketahanan Pangan dan Gizi Keluarga - Iseu Siti Aisyah; Neni Neni; Lesi Oktiwanti; Andi Eka Yunianto (Sarana Ilmu Indonesia (salnesia), 2022)
Food security and the problem of fulfilling nutrition during the Covid-19 pandemic are new problems in the community because people are required to do physical distancing so that the spread of the virus can be reduced. This study aimed to analyze the effect of health interventions with video tutorials on food security and family nutrition knowledge during the Covid-19 pandemic. This research was an experimental study with a group pre and post-test design with a sample of 70 people. This research was carried out in 4 villages in Tasikmalaya City, namely Sukahurip Village, Sumelap Village, Sukamaju Kidul Village, and Cipedes Village with several samples. The intervention in this study was the provision of video tutorials on how to obtain food needs through planting in polybags and cultivating budikdamber which were published on youtube and distributed via WhatsApp to the public. Based on the Paired Sample T-test Dependent test between pretest and posttest scores, p-value=0,000 (p-value<0,05), it can be concluded that there is a significant difference between knowledge about family food security before and after being given a video. Giving videos affects increasing subjects knowledge. Researchers suggest further studies on the practice of directly applying it in real life at home.